MODELING OF WATER BALANCE AND GROUND WATER LEVELS IN THE PEAT HIDROLOGY AREA IN PULANG PISAU DISTRICT, SUB KHG 1 AND 2 CENTRAL KALIMANTAN - Prasetya, Bagus
Agricultural development in Indonesia for the time being is done not only on dry land but also on wet / swampy land. Drainage development on peatlands causes the availability of water in peatlands to decrease, peat subsides, peatland ecosystems become damaged and peatlands are very vulnerable to fire, especially in the dry season. The purpose of this study is to analyze water balance in Pulang Pisau Regency and optimize groundwater level stability. From the results of calibration calculations, the hydraulic conductivity value of peat in Pulang Pisau District was 5.78x10-4 m/sec. Obtained the calibration value of modeling groundwater level with field data has good results, with a correlation value of 0.962 and an NSE value of 0.836. Canal water level is obtained by running in the HEC-RAS software with F.J.Mock debit input as boundary upstream and tidal as boundary downstream. The lowest water level of the canal at high tide occurred in March, which was 1.53 m and at low tide it occurred in November at 1.22 m. Groundwater level is modeled by Q-gis Freewat plugins software with boundary input distance between canals, channel length, canal water level, recharge, and evapotranspiration for one year. From the modeling carried out, there are several months that have groundwater conditions below the water level that is restricted, especially in the dry season the conditions recede, which is July-October. At high tide conditions, a minimum of 0.4 m of bulkhead is installed so that the water level in the ground remains in a safe condition. During low tide, 0.4-0.5 m Bulkhead is not able to raise the ground water level to a safe condition. Bulkhead height is required around 0.6 m so that all water level conditions are safe.